Follicular localization of growth differentiation factor 8 and its receptors in normal and polycystic ovary syndrome ovaries†. Issue 5 (2nd February 2018) - Lin, Ting-Ting; Chang, Hsun-Ming; Hu, Xiao-Ling; Leung, Peter C K; Zhu, Yi-Min
Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age and its etiology has not been characterized. Growth differentiation factor 8 (GDF8) is a member of the transforming growth factor-β superfamily that plays a critical role in the regulation of ovarian functions. However, the expression pattern of GDF8 in the human ovary is not yet clear. This study examined the cellular distribution of GDF8 and its putative cellular receptors (ACVR2A, ACVR2B, and ALK5) in a series of normal (n = 34) and PCOS ovaries (n = 14). The immunostaining of GDF8, ACVR2A, ACVR2B, and ALK5 was detected in the oocytes regardless of the developmental stage. All these proteins were localized in antral follicles in normal and PCOS ovaries, and the expression of these proteins increased with increasing follicle diameter. A significantly higher expression of GDF8 was detected in the granulosa cells than in the matched theca cells (TCs). These proteins were also localized in the luteal cells of the corpus luteum. Granulosa cells and TCs of large antral follicles in PCOS ovaries display a higher expression of these proteins. The higher expression levels of GDF8 and its functional receptors (ACVR2A, ACVR2B, and ALK5) in antral follicles of PCOS ovaries than those in normal ovaries suggest the possible involvement of dysregulated GDF8 in the pathogenesis of PCOS. Summary Sentence: Follicular localization of growth differentiation 8 and its receptor is increased in polycystic ovaries than in normal ovaries.